2020
DOI: 10.4041/kjod.2020.50.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical considerations for uprighting impacted mandibular molars

Abstract: This case report demonstrates two different uprighting mechanics separately applied to mesially tipped mandibular first and second molars. The biomechanical considerations for application of these mechanisms are also discussed. For repositioning of the first molar, which was severely tipped and deeply impacted, a novel cantilever mechanics was used. The molar tube was bonded in the buccolingual direction to facilitate insertion of a cantilever from the buccal side. By twisting the distal end of the cantilever,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Thus, an occlusal interference with the opposing tooth may occur. Morita et al suggested utilizing a compression force with a two-step bend incorporated into a NiTi archwire for cases in which the molar was slightly tipped and extruded [34].…”
Section: Orthodontic Uprighting Cantilever Springmentioning
confidence: 99%
“…Thus, an occlusal interference with the opposing tooth may occur. Morita et al suggested utilizing a compression force with a two-step bend incorporated into a NiTi archwire for cases in which the molar was slightly tipped and extruded [34].…”
Section: Orthodontic Uprighting Cantilever Springmentioning
confidence: 99%
“…Das Verhältnis von Extrusion und Aufrichtung kann dabei durch die Modifikation des Teilbogens gesteuert werden, da die Länge des Hebelarms direkt proportional zu der Größe des erzeugten Drehmoments ist 22 . Eine Erhöhung des Drehmoments kann folglich beispielsweise durch eine Extension des Hebels nach mesial, mit Anbindung mesial oder distal des Eckzahns statt zwischen den Prämolaren, erzielt werden 8 .…”
Section: Mechanikauswahlunclassified
“…Dabei stellen ausgedehnte kariöse Läsionen oder Restaurationen, die Molaren-Inzisiven-Hypomineralisation (MIH), apikale Pathologien und endodontische Probleme die Hauptursachen für den Verlust erster Molaren dar 3 4 5 . In Folge neigen Oberkiefermolaren eher zu Rotation und Elongation 6 7 8 , während bei Unterkiefermolaren meist eine mesiale Kippung festzustellen ist 7 9 . Aber auch Lückensituationen bei Nichtanlagen, Zahnwanderungen und Zahnverlust in Folge von Parodontitis können eine Kippung von Molaren bedingen.…”
Section: Introductionunclassified
“…Besides vertical activation, cantilevers can also be activated to produce a palatal as well as a buccal force [ 2 , 3 , 4 ]. They may serve as a simple system to solve multiple orthodontic problems [ 2 , 5 ], including frontal segment intrusion in deep bite correction [ 5 , 6 ] uprighting of tipped molars [ 7 , 8 ], intrusion of a single tooth [ 9 , 10 ], treatment of impacted teeth [ 11 , 12 , 13 , 14 , 15 ], correction of dental transposition [ 16 , 17 , 18 , 19 ], space closure [ 20 ], correction of occlusal plane cant [ 21 ] and dental asymmetries [ 22 ]. The commonly used material to manufacture cantilevers is titanium molybdenum alloy (TMA).…”
Section: Introductionmentioning
confidence: 99%